2015
DOI: 10.1016/j.ppees.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Community attributes determine facilitation potential in a semi-arid steppe

Abstract: Please cite this article as: Amat, B., Cortina, J., Zubcoff, J.J.,Community attributes determine facilitation potential in a semi-arid steppe., Perspectives in Plant Ecology, Evolution and Systematics (2014), http://dx.doi.org/10.1016/j.ppees. 2014.10.001 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Foundation species ameliorate climatic conditions or maintain resource levels above that of bare ground habitats, and their effects are often species-specific (Macek, Prieto, Macková, Pistón, & Pugnaire, 2016;Proffitt, Chiasson, Owens, Edwards, & Travis, 2005). The different microhabitats created by different co-occurring foundation species can then be colonized by distinct sets of subordinate species, resulting in higher community-level diversity (Amat, Cortina, & Zubcoff, 2015;Chen et al, 2015;Pistón et al, 2016).…”
mentioning
confidence: 99%
“…Foundation species ameliorate climatic conditions or maintain resource levels above that of bare ground habitats, and their effects are often species-specific (Macek, Prieto, Macková, Pistón, & Pugnaire, 2016;Proffitt, Chiasson, Owens, Edwards, & Travis, 2005). The different microhabitats created by different co-occurring foundation species can then be colonized by distinct sets of subordinate species, resulting in higher community-level diversity (Amat, Cortina, & Zubcoff, 2015;Chen et al, 2015;Pistón et al, 2016).…”
mentioning
confidence: 99%
“…Verdú and García‐Fayos () observed that trees act as perches for birds in abandoned crops in the southeastern Iberian Peninsula, and promoted nucleation via seed establishment beneath the perches. Likely, if birds continued to use branch piles long term at our site, persistent seed rain could foster seedling establishment in semiarid steppes where chances of spontaneous colonization are low (Amat et al ).…”
Section: Discussionmentioning
confidence: 99%
“…), attenuated thermal stress, insolation (Malkinson & Tielbörger ) and runoff water (Amat et al . ), increased infiltration (Pugnaire et al . ; Cecchi et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Amat et al . ; Tirado et al . ), there have been some exceptions (Bertness & Ewanchuk ; López et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation